Seawater Intrusion at the Grounding Line of Jakobshavn Isbræ, Greenland, From Terrestrial Radar Interferometry - Jae Hun Kim; Eric Rignot; David Holland; Denise Holland (Geophysical Research Letters)
Abstract Jakobshavn Isbræ, a major outlet glacier in Greenland, lost its protective ice shelf in 2002 and has been speeding up and retreating since. We image its grounding line for the first time with a terrestrial radar interferometer deployed in 2016 and detect its migration at tidal frequencies. The southern half of the glacier develops a floating section (3 km × 3 km) that migrates in phase with the tidal difference, up to a distance of 2.8 km, far more than previously expected. We attribute the migration to kilometer‐scale seawater intrusions, 10–20 cm in height, with the tide. The intrusions reveal that the glacier bed may be up to 800 m deeper than expected on the south side, which illustrates that our knowledge of bed topography remains limited for this glacier. We expect seawater intrusions to cause rapid melt of basal ice and play a major role in the glacier evolution.